Angiogenic Role of Mesothelium-Derived Chemokine CXCL1 During Unfavorable Peritoneal Tissue Remodeling in Patients Receiving Peritoneal Dialysis as Renal Replacement Therapy - Catar, Rusan Ali; Bartosova, Maria; Kawka, Edyta; Chen, Lei; Marinovic, Iva; Zhang, Conghui; Zhao, Hongfan; Wu, Dashan; Zickler, Daniel; Stadnik, Honorata; Karczewski, Marek; Kamhieh-Milz, Julian; et al. (Frontiers in Immunology, 2022)
Peritoneal dialysis (PD) is a valuable ‘home treatment’ option, even more so during the ongoing Coronavirus pandemic. However, the long-term use of PD is limited by unfavourable tissue remodelling in the peritoneal membrane, which is associated with inflammation-induced angiogenesis. This appears to be driven primarily through vascular endothelial growth factor (VEGF), while the involvement of other angiogenic signaling pathways is still poorly understood. Here, we have identified the crucial contribution of mesothelial cell-derived angiogenic CXC chemokine ligand 1 (CXCL1) to peritoneal angiogenesis in PD. CXCL1 expression and peritoneal microvessel density were analysed in biopsies obtained by the International Peritoneal Biobank (NCT01893710 at www.clinicaltrials.gov), comparing 13 children with end-stage kidney disease before initiating PD to 43 children on chronic PD. The angiogenic potential of mesothelial cell-derived CXCL1 was assessed in vitro by measuring endothelial tube formation of human microvascular endothelial cells (HMECs) treated with conditioned medium from human peritoneal mesothelial cells (HPMCs) stimulated to release CXCL1 by treatment with either recombinant IL-17 or PD effluent. We found that the capillary density in the human peritoneum correlated with local CXCL1 expression. Both CXCL1 expression and microvessel density were higher in PD patients than in the age-matched patients prior to initiation of PD. Exposure of HMECs to recombinant CXCL1 or conditioned medium from IL-17-stimulated HPMCs resulted in increased endothelial tube formation, while selective inhibition of mesothelial CXCL1 production by specific antibodies or through silencing of relevant transcription factors abolished the proangiogenic effect of HPMC-conditioned medium. In conclusion, peritoneal mesothelium-derived CXCL1 promotes endothelial tube formation in vitro and associates with peritoneal microvessel density in uremic patients undergoing PD, thus providing novel targets for therapeutic intervention to prolong PD therapy.